Propuesta de análisis interno de la empresa Banaplast fomentando el posicionamiento competitivo de mercado en la provincia de El Oro. - Granda Alvarado, Martha Paola (My University, 2019)
The productive companies to be able to differentiate themselves and to be competitiveness at global business level, must determine innovative strategies that allow them not only to position themselves within the market but to generate reliability towards the user. The objective of this work is to be able to determine the internal analysis of the company Banaplast S.A, located in the city of Machala province of El Oro, through the use of methodological tools that allow him to carry out an internal analysis of the strengths and weaknesses With which this account to take this as an analytical reference and thus determine those strengths as strategies of business sustainability. This process was carried out by using the tools of internal analysis that allowed to determine the variables of each functional area that the company counts, likewise, the use of the tool MEFI the same that impulse to the weighted determination of the analysis Internal strengths and weaknesses with this determining which are the most important strengths and weaknesses that should be corrected to create business competitiveness.
Las empresas productivas para poder diferenciarse y ser competitivas a nivel global empresarial, deben determinar estrategias innovadoras que les permitan no solo posicionarse dentro del mercado, sino generar confiabilidad hacia el usuario. El objetivo de este trabajo es poder determinar el análisis interno de la empresa Banaplast S.A, ubicada en la ciudad de Machala Provincia de El Oro, mediante el uso de Herramientas metodológicas que le permitan realizar un análisis interno de las fortalezas y debilidades con las que esta cuenta para tomar esto como referencia analítica y así determinar aquellas fortalezas como estrategias de sostenimiento empresarial. Se llevó a cabo este proceso mediante el uso de las herramientas de análisis interno que permitió determinar las variables de cada área funcional que cuenta la empresa, así mismo, El uso de la herramienta MEFI la mismas que impulsó a la determinación ponderada del análisis interno fortalezas y debilidades con ello determinando cuales son los puntos fuertes de mayor relevancia y los puntos débiles que se debe corregir para crear competitividad empresarial.
Keywords: ANÁLISIS INTERNO; COMPETITIVIDAD; POSICIONAMIENTO